MENINGKATKAN HASIL BELAJAR SISWA DENGAN MEMPERGUNAKAN METODE PROBLEM SOLVING PADA KELAS III SD NEGERI 12 CIMPARUH KOTA PARIAMAN - Elly Marius (Ensiklopedia Education Review, 2020)
This type of research is Classroom Action Research (CAR). Therefore, in accordance with classroom action research, the research problem that must be solved comes from the problem of learning practices in the classroom more professionally. The results of observations of observations in the first cycle of the implementation of problem solving methods experienced positive developments. namely in the first cycle the average activity of students 43% to 82% or an increase of 395%, while the learning outcomes of students in the first cycle averaged 65.36 with a mastery level reaching 46%. In the second cycle the average student learning outcomes were 85 and student completeness was 93%. From the results of the research carried out for 2 cycles by using the problem solving method, there was a good rise, so the implementation of the problem solving method was suitable for use in Thematic learning sub theme I.